Towards a complete understanding of the Magellanic Stream Formation. Issue 4 (9th May 2019) - Wang, Jianling; Hammer, Francois; Yang, Yanbin; Ripepi, Vincenzo; Cioni, Maria-Rosa L; Puech, Mathieu; Flores, Hector
ABSTRACT: The Magellanic Clouds (MCs) have lost most of their gas during their passage by the Milky Way, a property that has never been successfully modelled. Here, we use accurate and mesh-free hydrodynamic simulations to reproduce the Magellanic Stream and the MCs in the frame of a 'ram-pressure plus collision' model. This model reproduces many of the observed properties of the H i Stream including most of its density profile along its length and its dual filamentary structure. Besides this, ram-pressure combined with Kelvin–Helmholtz instabilities extracts amounts of ionized and H i gas consistent with those observed. The modelled scenario also reproduces the Magellanic Bridge, including the offset between young and old stars, and the collision between the Clouds, which is responsible of the very elongated morphology of the Small Magellanic Cloud along the line of sight. This model has solved most of the mysteries linked to the formation of the Magellanic Stream. The Leading Arm is not reproduced in the current model because it requires an alternative origin.